Examining variation in the measurement of multimorbidity in research: a systematic review of 566 studies - Ho, IS-S; Azcoaga-Lorenzo, A; Akbari, A; Black, C; Davies, J; Hodgins, P; Khunti, K; Kadam, U; Lyons, RA; McCowan, C; Mercer, S; Nirantharakumar, K; et al. (Elsevier, 2021)
Background A systematic understanding of how multimorbidity has been constructed and measured is unavailable. This review aimed to examine the definition and measurement of multimorbidity in peer-reviewed studies internationally.